Genesis Analysis of Volcanic Landforms and Spatial Potential of Babadan Village as a Contextual Geography Learning Resource - Siraj Abdulkerim Yaseen; Baihaki; Risky Andias Oktavian (Future Space: Studies in Geo-Education, 2026)
Volcanic landscapes represent immense potential as "natural laboratories" for geography education, yet micro-scale geomorphological data is rarely transposed into formal instructional praxis. This research analyzes the volcanic morphogenesis and land-use trajectories of Babadan Village, Malang, to formalize a conceptual framework for didactic transposition. Adopting an integrated spatial-explorative methodology, the study prioritizes geospatial discovery through Digital Elevation Model (DEM) extraction from Alos Palsar imagery and in situ analytical surveys. This approach serves as a Design-Based Research (DBR) precursor, utilizing purposive sampling based on landscape visibility and accessibility to identify representative observation sites for Field Study (KKL) modules. Spatial analysis delineates a tri-zonal volcanic configuration comprising volcanic slopes, foothills, and foot plains derived from the Quaternary Kawi-Butak sedimentary formation. Pedagogical results demonstrate that these units effectively operationalize core spatial thinking components, specifically spatial association (correlating lithological facies with land-use transitions) and scale-awareness (validating regional remote sensing data through micro-scale field observation). The socio-ecological shift toward elephant grass monoculture is identified as a critical Problem-Based Learning (PBL) object for evaluating environmental carrying capacity and land-use trade-offs. By streamlining geological technicalities, the study establishes an authentic geospatial database that bridges theoretical geomorphology with field-based spatial literacy. This research provides the necessary scientific infrastructure for subsequent empirical evaluations of students' higher-order spatial thinking, offering a rigorous model for contextual geography education in volcanic regions.